Mind Your Writing How to be a Professional Academic Writer - Wymann, Christian (Verlag Barbara Budrich, 2021)
In order to write and publish successfully, academic writers must be aware of their skills and their role as writers. They need to be able to answer fundamental questions about their writing, enabling them to make conscious and strategic decisions. Only in that way they will become writing professionals who successfully carry out their profession.